Gait Analysis through a visual method to calculate temporal parameters: comparison of performance between the gait laboratory and the clinical setting - de Grucci, Carla (2019)
Analysis of human movement providessystematic and quantitative information of movement. The detection of eventsthat occur during walking allows for the calculation of spatiotemporalparameters, commonly used for the characterization of gait. A method for visualdetection of gait events was previously evaluated, showing promising results.The method should now be used in the clinical setting for estimation of gaitparameters and symmetry. The aims of this study were then to compare theperformance of the visual method in a clinical setting against its performancein a gait laboratory and to evaluate its behavior for calculation of gaitsymmetry in eight healthy subjects. Two gait events were detected and sixtemporal parameters (TP) were calculated. Also, a symmetry index (SI) wascalculated for three TP. Results for the calculation of TP in the clinicalsetting were comparable to those obtained in the gait laboratory. Also, thevalues of TP and symmetry were within the range of those reported by otherauthors. These results suggest that the visual events detection method can beconsidered as an option for basic Analysis of Human Movement in the clinicalenvironment.